FALL RISK, FEAR OF FALLING, PHYSICAL ACTIVITY, AND SELF-PERCEPTIONS IN ETHNICALLY DIVERSE LOW-INCOME OLDER ADULTS. (20th December 2022) - Thiamwong, Ladda; Xie, Rui; Lighthall, Nichole; Park, Joon-Hyuk; Loerzel, Victoria; Stout, Jeffrey
Abstract: Falls and fear of falling (FOF) are the leading cause of disability, and hospitalization in ethnically diverse low-income older adults. The present study included an ethnically diverse sample of low-income older adults (N=121) to examine ethnic and income-based group differences in risk factors for falls (high FOF, depression, avoidance of physical activity) and the role of negative self-perceptions of aging in driving these risk factors. Results revealed the highest levels of fall risk among Hispanics and Asian Americans, FOF among African Americans, and depression among Hispanics. Accelerometer-based physical activity measures confirmed that low-income older adults had lower levels of moderate to vigorous physical activity (MVPA) compared with their high-income counterparts (p=0.04). Further, financial difficulty was related to MVPA (p<0.001), depression, anxiety, and fall risk (p=0.01). Critically, we also found a strong relationship between negative self-perceptions of aging and FOF (p = 0.002) across groups.